Epidemiological Behavior of Human Rabies in the State of Zulia, Venezuela, During the Surveillance Period: January, 1993 - June, 2009 - María Alcira Luzardo; Nelis del Pilar Barboza; Soledad Briceño; Cecilia López (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Rabies represents a major public health problem in the State of Zulia, constituting the entity with the highest incidence of animal and human cases in Venezuela, registering 25 human deaths by rabies from January, 1993 - June, 2009. The objective of this study is to describe its epidemiological behavior during this period; the epidemiological study was observational and descriptive. The sample included all cases confirmed as human rabies in the entity during this period (n = 25); they were between 2 and 57 years of age, from both sexes and 7 municipalities. Data was taken from the reports of rabies cases in the Regional Epidemiology Direction. The results are expressed in percentages, means, confidence intervals, mortality rate and distributions according to age, sex and municipality of occurrence. The highest incidence was in males (68%).The group between 2-10 years was principally affected (60%). Eighty per cent of the cases did not seek post-exposure consultation and did not receive timely prophylaxis. The direct fluorescent antibody test was used for diagnostic confirmation. Knowledge about forms of rabies transmission is crucial for its prevention; the time between viral inoculation and neural invasion is perhaps the only period for an effective prophylaxis.